Estudio de prefactibilidad para la instalación de una planta de producción de un batido en polvo a base de soya, cañihua y tarwi - Bocanegra Pizarro, Rocio Isabel (2019)
This paper determines the market, technological, economic and financial viability for the installation of a plant for the production of a powder shake based on Andean grains: tarwi, cañihua and soy.